Identification of marketing strategies to promote tourism: the case of Soetdoring Nature Reserve in the Free State province - Pholoana, Matshidiso Miklas (University of the Free State, 2020)
The purpose of this study was to investigate and identify marketing strategies to promote tourism at Soetdoring Nature Reserve located in the Free State Province. The primary question that was explored was what recommendations can be made with regard to marketing of the Soetdoring Nature Reserve. For research objectives to be achieved, an in-depth literature review was undertaken. Additionally, a survey was also conducted to determine the current status of the Soetdoring Nature Reserve and data were sourced by means of self-administered questionnaires. The hypothesis was proven to be correct by a literature review, namely that marketing plays a significant role in promoting tourism and has the potential of attracting tourists and raising revenue. The recommendations were made within the context of empirical survey findings. To improve the current marketing at the Soetdoring Nature Reserve, it has been recommended that there should be a turnaround marketing strategy and that resources in a form of funds and staff should be augmented. Furthermore, the 7Ps of marketing, which are of paramount importance, were also recommended, as well as that there more marketing should be done on social media and on the internet.
Dissertation (M.P.A. (Public Administration))--University of the Free State, 2020
Keywords: Tourism -- South Africa -- Free State; Tourism -- Marketing; Tourism -- Planning -- South Africa -- Free State